Isolation and characterization of genotype VII Newcastle disease virus from NDV vaccinated farms in Malaysia - Aljumaili, O. A.; Yeap, Swee Keong; Omar, Abdul Rahman; Ideris, Aini (Universiti Putra Malaysia Press, 2017)
Molecular analysis, particularly sub-genotype classification, and study on the relationship of recent Malaysian NDVs with other isolates from around the world are lacking. Therefore, in the present study, a molecular epidemiological investigation was conducted to characterise six Newcastle disease viruses (NDV) isolated between 2014 and 2015 from vaccinated commercial poultry flocks. Partial Fusion (F) and Hemagglutinin-neuraminidase (HN) genes were amplified from IBS046/2014, IBS060/2014, IBS061/2014, IBS074/2014, IBS160/2015, and IBS162A/2015 isolates using one-step reverse transcription polymerase chain reaction (RT-PCR), sequenced and phylogenetically analysed. Sequence and phylogenetic analysis revealed that all the recently isolated strains of NDV belonged to sub-genotype VIIa and lineage 5a. Moreover, deduced amino acid sequence at the F protein cleavage site of the isolates revealed either 112RRQKRF117 or 112KRRKRF117 consistent with the motif found in velogenic pathotypes. The study concluded that the genotype VIIa was the causative agent of recent ND outbreaks in vaccinated broiler flocks from Malaysia. Interestingly, five out of the six isolates characterised in this study had a unique F0 protein cleavage site (112KRRKRF117). Further studies are required to determine the role of these motifs on the virulent potential of the isolates.